The Longitudinal Profile of a Prograding River and Its Response to Sea Level Rise - Gao, Weilun; Li, Dongxue; Wang, Zheng Bing; Nardin, William; Shao, Dongdong; Sun, Tao; Miao, Chiyuan; Cui, Baoshan (Geophysical research letters, 2020)
River longitudinal profile, a key morphological characteristic of the river channel, is subject to river mouth progradation. Given the increasing influence of human activities and climate change on this critical downstream control, understanding its effects on the evolution of the longitudinal profile is imperative. A general theoretical framework is proposed to quantify the relevant effects, which is tested by numerical experiment and compared with field, numerical and laboratory data from the literature. The results suggest the existence of a critical ratio of accommodation space to sediment supply of approximately 0.5, above which the typical concave upward profile tends to form. Further analyses show that sea level rise tends to increase the concavity of the longitudinal profile of a river with a relatively low equilibrium bed slope and progradation rate. Plain Language Summary As a key feature of a river, the bed level along the river, i.e., the river longitudinal profile, affects flooding, navigation, etc., and thus greatly influences human societies and natural ecosystems. However, the effects of the seaward progradation of a river mouth on the evolution of the river longitudinal profile are still unclear. Given the increasing influence of human activities and climate change on this critical downstream control, understanding these effects becomes imperative. A new theoretical framework incorporating the effects of river mouth progradation on the evolution of a river longitudinal profile is developed and tested by numerical experiments, field observations, and numerical and laboratory data from the literature. The results show that the seaward progradation of a river mouth could potentially lead to the formation of a concave river longitudinal profile. Specifically, we found that there exists a critical condition in which the sediment supply is insufficient to balance the seaward progradation of the river mouth, causing the typical concave upward longitudinal profile to form. The proposed theoretical framework further suggests that sea level rise tends to increase the concavity of the longitudinal profile for river with a relatively low equilibrium bed slope and progradation rate. Key Points A theoretical framework is proposed for predicting the evolution of the longitudinal profile and its concavity of prograding rivers Numerical results suggest a critical ratio of accommodation space to sediment supply for the formation of a concave profile Sea level rise tends to increase the concavity of river profiles with a relatively low bed slope and progradation rate